EFFECT OF WIRE FEED RATE ON COATING FORMATION IN THE ARC SPRAYING PROCESS ARC SPRAYING - Molbosynov, Yermakhan (Вестник ВКТУ им. Д. Серикбаева, 2025)
. In this work, a study of steel coatings obtained by arc spraying using steel wire of the 30KhGSA grade has been carried out. The main attention is paid to the effect of the wire feed rate on the coating characteristics. The feed rate varied from 2 to 12 cm/sec. The results showed that an increase in the wire feed rate leads to a significant change in the coating characteristics. According to experimental data, a direct relationship was found between the wire feed rate and the coating thickness. At a speed of 2 cm/sec, the thickness was 108.4 μm, and at a maximum speed of 12 cm/sec — 733.62 μm. An increase in the feed rate led to a decrease in porosity. The highest porosity (10.45%) was observed at a minimum speed, whereas at a speed of 12 cm/sec, porosity decreased to 4.33%. The analysis of images obtained using a metallographic microscope revealed a layered structure of coatings with alternating light and dark phases. With an increase in the feed rate, the structure was compacted and the number of cracks decreased. X-ray diffraction analysis showed that the largest amount of oxides was formed at the minimum wire feed rate, whereas at the maximum speed oxidation was minimal. Hardness measurements by the Vickers method showed that with an increase in the wire feed rate, the hardness of the coating decreased, although different optimal values were observed for different structures. Optimal roughness values (Ra and Rz) were achieved at a feed rate of 4 cm/sec. Increasing the speed to 8 and 12 cm/sec led to a deterioration in surface roughness.